Juventudes: uma leitura sobre a interação entre estudantes universitários em Ouro Preto/MG - Juliano de Carvalho Fonseca (2016)
This study is the result of nearly three years of research conducted in a historic town and university, distant 100 km from the state capital. The transformation of Ouro Preto, in the nineteenth century, an important center of academic training provoked an intense and increasing migration of young people from other regions of the country, drawn above all by higher offer quality training and free , significantly changed the social setting of the old colonial city. This transformation, sometimes slow, sometimes fast, did not come unaccompanied small interactional des-arrangements, driven mainly by the absence of public facilities of sociability and the way found by the new residents to escape the monotony and bad, to interact with each other and narrow social ties, the party. Thus, the rock and the sociais parties are important between Ouro Preto youth, more evident among the residents of one of the more than 400 existing republics in the city. Thus, these frequent parties, seems to have developed a specific type of collective fantasy in the city, on the one hand, the local belief is that these outsiders do not respect the city and, much less, its residents "legitimate" and, on the other, the belief among students is that the locals live in the past and not open to the new, thus hindering the interaction between the young residents. That said, this study has as its main focus, this social relationship [imagined, difficult] among young people 18-29 years old, locals and floating residents, the latter, students of the University of Ouro Preto, aiming above all to grasp the logic that governs social relations developed in the city.